Research Progress on the NSP9 Protein of Porcine Reproductive and Respiratory Syndrome Virus - Sha, Huiyang; Zhang, Hang; Chen, Yao; Huang, Liangzong; Zhao, Mengmeng; Wang, Nina (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is a contact infectious disease caused by porcine reproductive and respiratory syndrome virus (PRRSV). PRRS is also called “blue ear disease” because of the characteristic blue ear of infected sows and piglets. Its main clinical features are reproductive disorders of sows and breathing difficulties of piglets and fattening pigs, which cause huge losses to the pig industry. NSP9, a non-structural protein of PRRSV, plays an important role in PRRSV replication and virulence because of its RNA-dependent RNA polymerase (RdRp) structure. The NSP9 sequence is highly conserved and contains T cell epitopes, which are beneficial for the development of future vaccines. NSP9, as the hub of protein interaction, participates in RNA replication and transcription, together with host proteins and self proteins. We here comprehensively review the application of NSP9 in terms of genetic evolution analysis, interaction with host proteins that affect virus replication, interaction with other viral proteins, pathogenicity, regulation of cellular immune response, antiviral drugs, vaccines, and detection methods. This review can therefore provide new ideas and methods for PRRSV prevention and control.